2014
DOI: 10.1111/bjep.12056
|View full text |Cite
|
Sign up to set email alerts
|

Incremental validity of WISCIVUK factor index scores with a referred Irish sample: Predicting performance on the WIATIIUK

Abstract: This, in combination with studies of apportioned variance from bifactor confirmatory factor analysis (Watkins et al., 2013, Int. J. Sch. Educ. Psychol., 1, 102), indicated that the WISC-IV(UK) FSIQ should retain the greatest weight in WISC-IV(UK) interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 91 publications
3
28
0
Order By: Relevance
“…Based on the present results and strong replication of previous findings , it seems prudent to focus WISC-IV UK interpretation on the FSIQ and if going beyond the FSIQ to interpret factor index scores (Wechsler based or CHC based) doing so with extreme caution so as not to misinterpret or over-interpret scores given the small unique variance provided by the group factors when conflated with general intelligence variance. Further examination of the WISC-IV UK should test relations to external variables or criteria, such as academic achievement, to determine what, if any, reliable achievement variance is incrementally accounted for by the WISC-IV UK factor index scores (or CHC constructs) beyond that accounted for by the FSIQ (see Canivez et al, 2014). Additionally, diagnostic utility studies should be conducted to ascertain the extent to which various factor indexes of the WISC-IV UK are able to correctly identify individuals from within various diagnostic groups that should hypothetically demonstrate differences in cognitive profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the present results and strong replication of previous findings , it seems prudent to focus WISC-IV UK interpretation on the FSIQ and if going beyond the FSIQ to interpret factor index scores (Wechsler based or CHC based) doing so with extreme caution so as not to misinterpret or over-interpret scores given the small unique variance provided by the group factors when conflated with general intelligence variance. Further examination of the WISC-IV UK should test relations to external variables or criteria, such as academic achievement, to determine what, if any, reliable achievement variance is incrementally accounted for by the WISC-IV UK factor index scores (or CHC constructs) beyond that accounted for by the FSIQ (see Canivez et al, 2014). Additionally, diagnostic utility studies should be conducted to ascertain the extent to which various factor indexes of the WISC-IV UK are able to correctly identify individuals from within various diagnostic groups that should hypothetically demonstrate differences in cognitive profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, the results of the present study only pertain to the latent factor structure and do not fully test the construct validity of the WISC‐V UK , which would involve examinations of relations with external criteria (Canivez, ). Examinations of incremental predictive validity (Canivez, ; Canivez, Watkins, James, James, & Good, ; Glutting, Watkins, Konold, & McDermott, ; Nelson, Canivez, & Watkins, ) to determine whether reliable achievement variance is incrementally accounted for by the WISC‐V UK factor index scores beyond that accounted for by the FSIQ score (or through latent factor scores [see Kranzler, Benson, & Floyd, ]) and diagnostic utility (see Canivez, ) studies should also be examined. Given the small portions of true‐score variance uniquely contributed by the four group factors in the WISC‐V UK standardization sample, it seems unlikely that WISC‐V UK factor index scores will provide meaningful value (DeMars, ).…”
Section: Discussionmentioning
confidence: 99%
“…This entry technique allows for the unique predictive effects of the lower-order scores to be assessed while controlling for the effects of the full-scale IQ score and operates conceptually in very much the same way as the Schmid and Leiman technique (1957) for residualizing variance in exploratory factor analysis. Incremental validity studies (e.g., Canivez et al, 2014;Glutting, Watkins, Konold, & McDermott, 2006;McGill &Busse, 2014;McGill, 2015) have consistently demonstrated that the omnibus full-scale score on intelligence tests accounts for most of the reliable achievement variance in prediction models and that little additional incremental variance is accounted for by lower-ordercognitive scores after controlling for the effects of the general factor. As a result, Canivez (2013) encouraged users of IQ tests to limit most, if not all, of their interpretation to the omnibus full-scale IQ score.…”
Section: Incremental Validitymentioning
confidence: 99%
“…As a consequence, interpreting all obtained scores may result in redundancy because clinicians are not able to disaggregate disparate sources of score variance at the level of the individual. Thus, consideration of the incremental validity of lower-order scores beyond that of higher-order scores is important when interpreting tests at multiple levels as is advocated for most contemporary cognitive measures (Canivez et al, 2014). …”
Section: Introductionmentioning
confidence: 99%